Protecting Rights in Common Law Constitutional Systems; a Framework for a Comparative Study - Saunders, Cheryl (Victoria University of Wellington Law Review, 2002)
This article discusses the changes that have taken place in common law constitutionalism in relation to the protection of rights, broadly defined. The first half of the article explores the way in which four common law nations that expressly protect rights in legislative or constitutional form: New Zealand, Canada, South Africa, and the United Kingdom. The author discusses how the four nations balanced core rights with citizen representation. The second half of the article then explores a common law nation without such protection: Australia. The author argues that the Australian approach demonstrates the impact of constitutionally diffusing power on the protection of rights; once allowance is made for the effects of Australia's written Constitution, rights protection depends on the interplay of political forces in majoritarian parliamentary systems and (to a lesser extent) common law principles applied by independent courts. The author concludes that all nations listed above take a different approach to protecting rights. Notably, Australia provides an interesting study while the author also comments that they have much to learn from the experience of the other four nations.